The role of honey in the ecology of the hive: Nutrition, detoxification, longevity, and protection against hive pathogens - Fernandes, Kenya E.; Frost, Elizabeth A.; Remnant, Emily J.; Schell, Kathleen R.; Cokcetin, Nural N.; Carter, Dee A. (Frontiers in Nutrition, 2022)
Honey is the source of energy for the European honey bee, Apis mellifera. Beyond simple nutrition and a hedge against the seasonal, geographic, and chemical unpredictability of nectar, honey has properties that protect the hive against various stresses. Enzyme-mediated detoxification during honey ripening neutralises potentially toxic phytochemicals, and bees that consume honey have enhanced tolerance to other ingested toxins. Catalase and antioxidant phenolics protect honey bees from oxidative damage caused by reactive oxygen species, promoting their longevity. Phytochemical components of honey and microRNAs have the potential to influence developmental pathways, with diet playing a large role in honey bee caste determination. Components of honey mediate stress response and promote cold tolerance during overwintering. Honey has a suite of antimicrobial mechanisms including osmotic pressure, low water activity, low pH, hydrogen peroxide, and plant-, honey bee-, and microbiota-derived compounds such as phytochemicals and antimicrobial peptides. Certain types of honey, particularly polyfloral honeys, have been shown to inhibit important honey bee pathogens including the bacteria responsible for American and European Foulbrood, the microsporidian Nosema ceranae, and the fungi responsible for Stonebrood. Understanding the diverse functional properties of honey has far-ranging implications for honey bee and hive health and management by beekeepers.